High yield purification and first structural characterization of the full‐length bacterial toxin CNF1. (14th November 2017) - Colarusso, Andrea; Caterino, Marco; Fabbri, Alessia; Fiorentini, Carla; Vergara, Alessandro; Sica, Filomena; Parrilli, Ermenegilda; Tutino, Maria Luisa
Abstract : The Cytotoxic Necrotizing Factor 1 (CNF1) is a bacterial toxin secreted by certain Escherichia coli strains causing severe pathologies, making it a protein of pivotal interest in toxicology. In parallel, the CNF1 capability to influence important neuronal processes, like neuronal arborization, astrocytic support, and efficient ATP production, has been efficiently used in the treatment of neurological diseases, making it a promising candidate for therapy. Nonetheless, there are still some unsolved issues about the CNF1 mechanism of action and structuration probably caused by the difficulty to achieve sufficient amounts of the full‐length protein for further studies. Here, we propose an efficient strategy for the production and purification of this toxin as a his‐tagged recombinant protein from E. coli extracts (CNF1‐H8). CNF1‐H8 was expressed at the low temperature of 15°C to diminish its characteristic degradation. Then, its purification was achieved using an immobilized metal affinity chromatography (IMAC) and a size exclusion chromatography so as to collect up to 8 mg of protein per liter of culture in a highly pure form. Routine dynamic light scattering (DLS) experiments showed that the recombinant protein preparations were homogeneous and preserved this state for a long time. Furthermore, CNF1‐H8 functionality was confirmed by testing its activity on purified RhoA and on HEp‐2 cultured cells. Finally, a first structural characterization of the full‐length toxin in terms of secondary structure and thermal stability was performed by circular dichroism (CD). These studies demonstrate that our system can be used to produce high quantities of pure recombinant protein for a detailed structural analysis. © 2017 American Institute of Chemical Engineers Biotechnol. Prog., 34:150–159, 2018